Ecological distribution of nematopalaemon schmitti and exhippolysmata oplophoroides (Crustacea: Caridea) near an upwelling area off southeastern Brazil - Herrera, Daphine Ramiro [UNESP]; Pescinelli, Regis Augusto [UNESP]; da Costa, Rogerio Caetano [UNESP] (Pontificia Universidad Catolica de Valparaiso, 2017)
Regions affected by upwelling show environmental characteristics that may change the distribution of the species. This study evaluated the influence of environmental factors on the spatiotemporal distribution of two caridean shrimps, Nematopalaemon schmitti and Exhippolysmata oplophoroides, in a region of the Brazilian coast affected by Cabo Frio upwelling. Shrimps were collected monthly from July 2010 through June 2011 off Macaé off the northern coast of Rio de Janeiro State, at six locations: three at 5 m, and the other three at 15 m depth. Shrimp abundance was compared among seasons and sampling sites. Nematopalaemon schmitti (n = 1200) was more abundant at 5 m depth while E. oplophoroides (n = 2176) occurred predominately at 15 m. There were significant seasonal fluctuations in the distribution of the species in the region, resulting from variation in bottom temperature. The presence of the South Atlantic Central Water (SACW) favors the decrease in the abundance of N. schmitti and highest abundance of E. oplophoroides. The abundance of E. oplophoroides and the percentage of organic matter were significantly and positively correlated. The organic matter content in the sediment and water temperature was among the most important variables affecting seasonal distribution of the species. The distinct environmental characteristic between the bathymetric regions were a determinant factor in their spatial distribution.
Keywords: Abiotic factors; Abundance; Exhippolysmata oplophoroides; Habitat; Nematopalaemon schmitti; Rio de Janeiro; SACW; Spatio-temporal distribution